Little prayers - Wilkin, Esther Burns; Wilkin, Eloise Burns (New York : Golden Press ; Racine, Wis. : Western Pub. Co., 1980)
A collection of prayers and poems from various countries and religions.
Keywords: Children -- Prayers and devotions; Prayers